حامكا وجهوده فى تفسير القرآن الكريم بإندونيسيا فى كتابه الأزهر (State Islamic University (UIN) of Sunan Ampel Surabaya, 2009)
A great Indonesian scholar, Hamka was a politician, novelist, cultural activist and above all religious scholar. His scholarly works cover so many different areas, but he was most well-known as a Qur’anic interpreter. His al-Azhar, a book of Qur’anic interpretation has won him both fame and respect up to this time in Indonesia and abroad. This paper is particularly interested in exploring the content of this book and in discussing the basic ideas underlining it. It is also interested in discussing the method of Hamka in tafsir, fiqh, the general characteristics of the book as well as the epistemological relationship between al-Azhar and especially al-Manar by a great Egyptian scholar, Muhammad `Abduh. The paper particularly argues that Hamka and his thought have exerted a great influence on social, cultural, and intellectual aspect in Indonesia.